GAMBARAN SIKAP ORANG TUA TENTANG PENCEGAHAN KEKERASAN SEKSUAL PADA ANAK USIA PRASEKOLAH DI DUSUN PRINGWULUNG CONDONGCATUR SLEMAN YOGYAKARTA - Irchama Budi Darmawan; Budhy Ermawan; Yustiana Olfah (Caring : Jurnal Keperawatan, 2017)
Sexual abuse is one type of violence involving children in sexual activity where children are not capable of giving consent against such activities. The development of sexual in preschool-aged children strengthen the sense of gender identity and began to distinguish the behavior of the appropriate gender. Parents who became the role model for a child, the role of parents is important in teaching, educating children in an early stage. Child sexual abuse can occur due to the attitude of parents that reflects the support of the occurrence of child sexual abuse. The purpose of this research is to determine the attitude of parents about the prevention of sexual abuse on children a preschool. This research is descriptive research with survey method in the year 2017. The population of this research is 51 parents who have preschool child in Pringwulung Condongcatur. The samples are taken use cluster sampling technique. The data taken by questionnaire. Analysis of the data using frequency distribution and presented in the form of a table. The results showed 33 respondents (64.7%) have a positive cognitive components, 35 respondents (68.6%) have a positive affective components, 30 respondents (58.8%) have a positive konatif components. The description of the attitude of parents about the prevention of sexual abuse on child a preschool have a positive attitude as much as 29 respondents (56.9%). Based on the result of the research can be concluded that the attitude of parents about sexual abuse on child a preschool in Pringwulung most of the positive (supportive).